Nonanatomic Posterolateral Tenodesis for Posterior Ligament Reconstruction Augmentation - Emiliano Álvarez-Salinas, M.D.; Leandro Civetta, M.D.; Javier Reparaz, M.D.; Joan Carles Monllau, M.D., Ph.D.; Rodolfo Morales-Avalos, M.D., M.Sc., Ph.D. (Arthroscopy Techniques)
A successful posterior cruciate ligament (PCL) reconstruction depends on multiple factors. Various techniques have been described for PCL reconstruction. Despite the constant evolution of reconstructive techniques, 26% of residual laxity cases with grade I and II positive posterior drawer tests have been reported in the literature in patients undergoing PCL reconstruction. Part of these failures is associated with the lack of control of the posterior translation of the tibia and the increase in external tibial rotation. We describe a surgical technique in which a posterolateral tenodesis augmentation associated with a single-bundle reconstruction of the PCL is performed. It is proposed for use in isolated reconstructions of the PCL in cases of grade III ruptures associated with or unassociated with low-grade posterolateral corner injuries.